The waterbodies of the halo-volcanic Dallol complex: earth analogs to guide us, where to look for life in the universe - Moors, Hugo; De Craen, Mieke; Smolders, Carla; Provoost, Ann; Leys, Natalie (Frontiers in Microbiology, 2023)
Microbes are the Earth life forms that have the highest degree of adaptability to survive, live or even proliferate in very hostile environments. It is even stated that microbes can cope with any extreme physico-chemical condition and are, therefore, omnipresent all over the Earth: on all the continents, inside its crust and in all its waterbodies. However, our study suggests that there exists areas and even water rich environments on Earth where no life is possible. To support the fact that water rich environments can be lifeless, we performed an extensive survey of ten different hyper extreme waterbodies of the halo-volcanic Dallol complex (Danakil depression, Ethiopia, Horn of Africa). In our study, we combined physico-chemical analyses, mineralogical investigations, XRD and SEM-EDX analyses, ATP measurements, 16S rDNA microbial community determinations and microbial culturing techniques. According to our findings, we suggest that the individual physico-chemical parameters, water activity and kosmo-chaotropicity, are the two most important factors that determine whether an environment is lifeless or capable of hosting specific extreme lifeforms. Besides, waterbodies that contained saturated levels of sodium chloride but at the same time possessed extreme low pH values, appeared to be poly-extreme environments in which no life could be detected. However, we clearly discovered a low diversity microbial community in waterbodies that were fully saturated with sodium chloride and only mildly acidic. Our results can be beneficial to more precisely classify whole or certain areas of planetary bodies, including water rich environments, as either potentially habitable or factual uninhabitable environments.